Peran Humas Dalam Pemanfaatan Instagram @kankeranakindonesia Untuk Mempertahankan Reputasi Yayasan Kanker Anak Indonesia - Nurdianti, Nunu; Alamsyah, Alamsyah; Suseno, Ari (Pascasarjana Institut Agama Islam Sunan Giri Ponorogo, 2025)
This study aims to analyze the role of public relations in utilizing the @kankeranakindonesia Instagram account to maintain the reputation of the Indonesian Child Cancer Foundation using descriptive qualitative research methods and public relations theory. The results showed that the role of public relations in managing the Instagram account is very important to maintain the foundation's reputation, as well as ensuring transparency and accountability in its activities. Public relations is directly involved in managing the uploaded content, as well as interacting with the public through comment sections and direct messages (DM). In addition, PR also plays a role in handling issues that arise on the platform so as not to negatively impact the foundation's reputation. Nonetheless, this study found that there are barriers to implementation, especially related to misunderstandings in the delivery of information between internal parties within the foundation.